Pelatihan Pembuatan Media Pembelajaran Berbasis CANVA bagi Guru MAS Nurul Maulid Muara Panas - Hidayat, Taufiq; Rahmat, Hayatul Khairul (PT Hakhara Akademia Indonesia, 2023)
This community service activity aimed to improve the digital teaching media competencies of teachers at MAS Nurul Maulid Muara Panas through Canva-based training. The two-day interactive workshop guided participants in learning, practicing, and integrating Canva into their teaching strategies. The results indicated a significant improvement in teachers' ability to design creative and engaging educational media. Canva has proven to be an innovative tool that supports active, visual, and collaborative learning within the madrasah environment.